2020
DOI: 10.3390/biom10091303
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K in Vertebrates’ Reproduction: Further Puzzling Pieces of Evidence from Teleost Fish Species

Abstract: Vitamin K (VK) is a fat-soluble vitamin that vertebrates have to acquire from the diet, since they are not able to de novo synthesize it. VK has been historically known to be required for the control of blood coagulation, and more recently, bone development and homeostasis. Our understanding of the VK metabolism and the VK-related molecular pathways has been also increased, and the two main VK-related pathways—the pregnane X receptor (PXR) transactivation and the co-factor role on the γ-glutamyl carboxylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 173 publications
(316 reference statements)
1
11
0
Order By: Relevance
“…Vitamin K, known to be a key element in the synthesis of active coagulation factors and involved in blood clotting, was also reported to have a biological function in reproduction. 10 In our study, vitamin K was found to be positively associated with the irregular menstrual cycle, especially the long menstrual cycle, which has not been reported before. In the context of the female reproductive system, vitamin K antagonists were reported to increase the risk of heavy menstrual bleeding.…”
Section: Discussionsupporting
confidence: 47%
“…Vitamin K, known to be a key element in the synthesis of active coagulation factors and involved in blood clotting, was also reported to have a biological function in reproduction. 10 In our study, vitamin K was found to be positively associated with the irregular menstrual cycle, especially the long menstrual cycle, which has not been reported before. In the context of the female reproductive system, vitamin K antagonists were reported to increase the risk of heavy menstrual bleeding.…”
Section: Discussionsupporting
confidence: 47%
“…20 In the mammalian ovary, LH targets theca cells of antral follicles to stimulate steroidogenesis, elevating the gene levels of STAR, CYP11A1, HSD3B1, HSD3B2, and CYP17A1 through PKA signaling and synthesizing androgens and progesterone. 49 The expression of STAR and CYP17A1 enables theca cells to synthesize androgens at the secondary follicle stage. 50 Cells expressing STAR and CYP17A1 offer a possibility of the presence of theca cells.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment is critical to implement the effective use of nutrients and feed additives at the farm level. Regarding VK, several articles revealed the biological function and the associated mechanisms in fish species [ 12 , 13 , 14 , 15 , 16 , 18 , 19 , 46 ]. However, little is known on how storing conditions might affect their maintenance in the short and long term [ 47 , 48 , 49 ], which is basic in providing practical guidelines to the industries.…”
Section: Discussionmentioning
confidence: 99%